Polymer brush decorated nanoparticles immobilised on polymer monoliths for enhanced biopolymer elution. Issue 32 (5th April 2017) - Iacono, M.; Connolly, D.; Heise, A.
Abstract : Polymer monoliths uniformly covered with polymer brush nanoparticles are fabricated and the elution properties investigated with myoglobin and blue dextran. Abstract : A protocol for the decoration of a polymeric monolith with polymer brush grafted silica nanoparticles was developed. Monolithic poly(glycidyl methacrylate- co -ethylene glycol dimethacrylate) (GMA- co -EDMA) was prepared in 15 mm long cylindrical polypropylene tubing and quarternized. 160 nm silica nanoparticles with a 20 nm poly(methacrylic acid- co-tert -butyl methacrylate) brush layer were flushed through the monolith and electrostatically trapped. A uniform and dense carboxylic acid containing brush nanoparticle surface decoration over the entire length of the monolith was achieved. Elution performance of the brush nanoparticle decorated monolith was compared to a carboxylic acid surface decorated monolith using myoglobin and blue dextran analytes. Quantitative analysis of critical elution parameters confirms an elution enhancement of the brush nanoparticle system, which is higher than expected from simple geometrical considerations of surface area increase and thus an effect of the polymer brush on the nanoparticle. The presented proof of concept offers a highly adaptable platform as polymer brushes of a broad spectrum (functional groups, hydrophilicity, etc. ) are readily accessible offering the opportunity to tailor monolithic surfaces towards the extraction problem.